2020
DOI: 10.1044/2020_jslhr-19-00117
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State Functional Magnetic Resonance Imaging Connectivity Between Semantic and Phonological Regions of Interest May Inform Language Targets in Aphasia

Abstract: Purpose Brain imaging has provided puzzle pieces in the understanding of language. In neurologically healthy populations, the structure of certain brain regions is associated with particular language functions (e.g., semantics, phonology). In studies on focal brain damage, certain brain regions or connections are considered sufficient or necessary for a given language function. However, few of these account for the effects of lesioned tissue on the “functional” dynamics of the brain for language pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 86 publications
1
7
0
Order By: Relevance
“…Ictal aphasia associated with this location has been reported 13 highlighting its potential role as a key node for language. In the present report, additional data is provided supporting the existence of a language network connecting Wernicke's area, Broca's area, and the basal temporal region, as postulated in connectivity studies 14 . These findings may question the prevalent hypothesis of a basal temporal area specific to semantic aspects of language, and highlight the complexity of a network with cortical and subcortical hubs, and both excitation and inhibition phenomena.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Ictal aphasia associated with this location has been reported 13 highlighting its potential role as a key node for language. In the present report, additional data is provided supporting the existence of a language network connecting Wernicke's area, Broca's area, and the basal temporal region, as postulated in connectivity studies 14 . These findings may question the prevalent hypothesis of a basal temporal area specific to semantic aspects of language, and highlight the complexity of a network with cortical and subcortical hubs, and both excitation and inhibition phenomena.…”
Section: Discussionsupporting
confidence: 71%
“…In the present report, additional data is provided supporting the existence of a language network connecting Wernicke's area, Broca's area, and the basal temporal region, as postulated in connectivity studies. 14 These findings may question the prevalent hypothesis of a basal temporal area specific to semantic aspects of language, and highlight the complexity of a network with cortical and subcortical hubs, and both excitation and inhibition phenomena. Moreover, an extended network must be involved to explain a more widespread deactivation response as shown in Patient 3.…”
Section: Discussionmentioning
confidence: 98%
“…To compensate, an increased activation of the right aINS may also occur ( 36 ). Ramage et al ( 65 ) used the same data set as New et al to study a network of brain regions considered as key regions for semantic and phonological processing in post stroke aphasia. Their results indicated that ipsilateral connections between temporal and frontal regions in both the left and the right hemisphere could predict access to semantic and phonological representations that serve as a basis for speech production.…”
Section: Discussionmentioning
confidence: 99%
“…The auditory information is first transmitted to the temporalparietal-occipital association cortex, of which the AG is the center, and then transmitted to the Wernicke's area. Ramage et al (52) demonstrated that connections between the left AG and left ITG was the only significant predictor of auditory comprehension scores in chronic aphasia patients. The occipital lobe is thought to be mainly related to visual information integration.…”
Section: Discussionmentioning
confidence: 99%